DIVINDADES MLK E CULTO A MOLEK NOS QUADROS DA CRISE RELIGIOSA NO FINAL DA MONARQUIA DE JUDÁ (2 Reis 16,3; 17,17.31; 21,6; 23,10; KTU 1.100; 1.118; 1.161) - Barbosa, Samuel Rodrigues (2004)
The dissertation is addressed to a special and unsolved problem in the description of Israel´s religious development. In Old Testament texts about the human sacrifices, there are autonomous literary units regarding the mOlek cult. However, some scholars claim that the mOlek cult has not such character. The dissertation aspires to scrutinize this argument, focusing on historical sources (2Kings 16,3; 17,17.31; 21,6; 23,10). Discussing ugaritic sources two deities list and one funerary text , we will inquiry about the characteristics of mlK deities at cannanite cultures. Briefly, the mOlek is a ctonic deity but it is not a recipient of human sacrifices.(AU)